Should Medical Students Be Overprotected? A Survey from China and Review About the Roles of Medical Student Under the COVID-19 - Qian F; Zhang S; Patel DM; Li Y; Jiao J (Risk Management and Healthcare Policy, 2023)
Fenghua Qian,1 Shanshan Zhang,2 Deepali M Patel,2 Yifang Li,2 Jian Jiao2 1Department of Education and Training, China-Japan Union Hospital, Jilin University, Changchun, People’s Republic of China; 2Department of Gastroenterology & Hepatology, China-Japan Union Hospital, Jilin University, Changchun, People’s Republic of ChinaCorrespondence: Jian Jiao, Department of Gastroenterology & Hepatology, China-Japan Union Hospital, Jilin University, Changchun, People’s Republic of China, Tel +86 13756009567, Email jjian@jlu.edu.cnObjective: The impact of COVID-19 continues to this day, there are many disputes about how medical students should be managed and diverse arrangements were adopted by medical schools around all over the world. The purpose of this study was to discuss the risks and benefits of medical student participation in healthcare in the context of COVID-19.Methods: An online cross-sectional survey was distributed to 300 Medical students undergoing standardized training program (STP) in China-Japan Union Hospital of Jilin University. The survey included questions about basic demographic characteristics, roles and mental state of interns during the pandemic, comments on the University’s management of medical students. Data were processed using SPSS 25.0 statistical analysis software, the comparison between two groups of data was performed using t-test; the non-normally distributed variables were analyzed using Mann–Whitney U-test, differences between groups were compared using chi-square test for analysis. p < 0.05 was considered statistically significant.Results: A total of 191 students completed the survey (response rate 63.67%). The epidemic had a significant psychological impact on students, but most of them believed that participation in clinical work under voluntary, precise protective measures and strict supervision were benefit for their future. Older, married, female, and salaried students are more willing to engage in pandemic-related activities. The biggest challenge of working under the pandemic focused on high working pressure and insufficient protection, the biggest harvest was getting knowledge and accumulating experience.Conclusion: Circumstances, cultures, outbreaks and strategies for coping with COVID-19 varied around the world. Medical students do not need to be overprotected, participation in pandemic work in an optimized system is acceptable and beneficial to their career plan. Medical education should focus on improving the social status of infectious diseases and cultivating future doctors with awareness of epidemic prevention and control.Keywords: medical student, response, psychological, the novel coronavirus disease (COVID-19)